PENGARUH PENGGUNAAN LABEL HALAL DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN UNTUK PEMBELIAN PIRANTI MASAK - ALOYSIUS RANGGA ADITYA NALENDRA; SLAMET HERI WINARNO; AGUS PRIADI (FE Program Studi Manajemen, 2021)
Halal certification programs for various types of products, both food and non-food, have become a necessity at this time, as a form of corporate responsibility in marketing products that are safe for use. It is believed that halal labeling on each brand will be able to be a determining factor for consumers to buy goods. However, to what extent is the effectiveness of this, it is necessary to research to prove it. This study aims to find the relationship or influence of halal labeling and the quality of non-food product brands on purchasing decisions, especially Teflon Maxim products. The method used in this research is descriptive quantitative using correlation analysis techniques that determine the level of relationship and influence between variables. The results showed that partially the halal label (X1) and product quality (X2) variables had a significant effect on purchasing decisions, as well as simultaneously the two variables showed a significant effect on purchasing decisions, as well as answering the proposed hypothesis.